Manajemen Konflik Di Tengah Dinamika Pondok Pesantren Dan Madrasah - Bashori Bashori (Muslim Heritage, 2016)
Abstract: In the dynamics of Islamic education institutions, certainly there will be any turmoil or conflict, either conflict between individual or conflict between groups. Recognized or not, the Islamic educational institutions, particularly pondok pesantren and madrasah, have the possibility of conflict is quite high compared with other educational institutions. From that assumption, this article aims to analyze the role of conflict management in resolving conflicts in the scope of Islamic educational institutions. Based on the study of theory, it can be concluded that the conflict management to be very central in developing the conflicts that exist in educational institutions Islamic school as a way to develop Islamic educational institutions for the better. In addition, because it has become a necessity that the conflict can not be avoided, then controlling the conflict becomes imperative in order to achieve objectives in Islamic educational institutions Abstrak: Dalam dinamika lembaga pendidikan Islam, pasti munsul gejolak atau konflik, baik konflik secara individu maupun konflik secara kelompok. Diakui atau tidak, lembaga pendidikan Islam khususnya pondok pesantren dan madrasah, memiliki kemungkinan konflik yang cukup tinggi dibandingkan dengan lembaga pendidikan yang lain. Dari asumsi itulah tulisan ini bertujuan menganalisis peranan manajemen konflik dalam menyelesaikan konflik yang terjadi di lingkup lembaga pendidikan Islam. Berdasarkan kajian teori, dapat disimpulkan bahwa manajemen konflik menjadi sangat sentral dalam mengembangkan konflik yang ada di lembaga pendidikan pondok pesantren dan madrasah sebagai cara dalam mengembangkan lembaga pendidikan Islam menjadi lebih baik. Selain itu, karena sudah menjadi keniscayaan bahwa konflik tidak dapat dihindari, maka mengendalikan konflik menjadi keharusan demi mencapai tujuan dalam lembaga pendidikan Islam.